AD, Volume 41, n° 4, 2016 - Full Issue (Africa Development, 2021)
Selected papers from the 13th CODESRIA General Assembly Contents / Sommaire Mulheres e HIV/SIDA: Os Silêncios e as Vozes em Moçambique, Africa do Sul e Brasil – Políticas públicas e acesso aos serviços de saúde Isabel Maria Casimiro .............................1 Healthcare Delivery and the Limits of the National Health Insurance Scheme in Nigeria Alex E. Asakitikpi......................29 Care for Older Persons in Cameroon: Alternatives for Social Development Ethel Ngere Nangia ....................... 47 Politics of Natural Resource Management and Accountable Systems in the Delivery of Water Services in Uganda John Mary Kanyamurwa ................................. 71 Institutional Design and the Implementation of the African Peace Security Architecture in Eastern Africa Sabastiano Rwengabo ....................... 107 Conflict between National Interest and Human Rights: Britain’s Policy towards African Immigrants, 1960 – 2013 James Olusegun Adeyeri and Jacob Olayemi Ogunniyi ............ 139 Hidden Processes of Reconciliation in Mozambique: The Entangled Histories of Truth-seeking Commissions held between 1975 and 1982 Maria Paula Meneses ...........................153